ENHANCING ELEMENTARY EFL LEARNERS’ UNDERSTANDING OF TIME EXPRESSIONS THROUGH INTERACTIVE WORKSHEETS - Fitriani, Novelia; Margono, Angelia; Faradilla, Masda Egy; Hamidah, Siti; Syahid, Abdul; Suriandari, Heny (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Understanding time concepts and their linguistic expressions remains a significant challenge for elementary EFL learners due to the lack of engaging and contextual learning materials. This Classroom Action Research aimed to enhance Grade III students’ mastery of